Formalization of medical informatics UML and Z specifications - Rajoo, Mageswari (Fakulti Sains dan Teknologi, 2011)
UML is a standard graphical modeling language; it presents a set of notation for visualizing, specifying, constructing, and documenting a software-intensive system. But UML is not a formal language; it is composed by graphical notation and natural language. To improve software reliability and reusability, the use of formal specification is necessary.